2015
DOI: 10.1007/s00228-015-1915-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NAD(P)H quinone oxidoreductase 1 polymorphisms on stable warfarin doses in Korean patients with mechanical cardiac valves

Abstract: Our results demonstrate that NQO1 gene polymorphisms influence stable warfarin doses in Korean patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The rs2364723 (C107G) polymorphism was associated with reduced risk of cardiovascular mortality [ 12 ]. The NQO1 gene polymorphism rs1800566 (C609T) is characterized by the replacement of proline by serine at position number 187 of the functional protein, which causes destabilization and inactivation of the enzyme [ 13 , 14 ]. The rs1800566 polymorphism has been associated with lower levels of blood coagulation factors [ 15 ], higher risk of coronary artery disease in T2DM patients [ 16 , 17 ], and increased triglycerides levels and decreased HDL-C levels in individuals with metabolic syndrome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rs2364723 (C107G) polymorphism was associated with reduced risk of cardiovascular mortality [ 12 ]. The NQO1 gene polymorphism rs1800566 (C609T) is characterized by the replacement of proline by serine at position number 187 of the functional protein, which causes destabilization and inactivation of the enzyme [ 13 , 14 ]. The rs1800566 polymorphism has been associated with lower levels of blood coagulation factors [ 15 ], higher risk of coronary artery disease in T2DM patients [ 16 , 17 ], and increased triglycerides levels and decreased HDL-C levels in individuals with metabolic syndrome [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given this evidence and the once putative role of NQO1 in vitamin K recycling, we and others have examined warfarin dose requirements by the NQO1*2 genotype with mixed results. Although no association has been identified in European or African ancestry populations, 19,40 accumulating data suggest an association in some Latino and Asian populations; although data are not entirely consistent 19,22,41,42 …”
Section: Discussionmentioning
confidence: 99%
“…Although no association has been identified in European or African ancestry populations, 19,40 accumulating data suggest an association in some Latino and Asian populations; although data are not entirely consistent. 19,22,41,42 Latinos who have varying European, African, and Native American ancestral composition share certain haplotypes with Asians, 43 in whom NQO1 associations with warfarin were documented. Our U.S. cohort included Latinos from the UAZ, who are presumably of mostly Mexican descent, as suggested by the genetic ancestry analysis, and UIC, who we previously reported were of predominantly Mexican descent, 19 with mostly European and Native American ancestry.…”
Section: Genetic Warfarin Determinants In Latinosmentioning
confidence: 99%
“…Studies in Caucasians and African-Americans show that CYP2C9 , [5] VKORC1 , [68] CYP4F2 , [9] EPHX1 , [10] CALU , [11] APOE , [12,13] and PROC [14] polymorphisms can significantly affect interindividual variability of warfarin dosing. In addition, several studies in Asian populations have found that polymorphisms in GGCX , [15,16] NQO1 , [17] and HNF4α [18] are also associated with warfarin dosing, indicating that gene polymorphisms affecting warfarin dose requirements vary among different racial groups. The genetic makeup of the Chinese population differs from that of other ethnic groups; therefore, novel gene loci influencing warfarin dosing were found in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%